Penerapan dan Produktivitas Input pada Usahatani Kentang - Suminartika, Eti; Rachmawati, Erna; Budiman, Muhammad arief Arief; Rahma, Ulya (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2026)
Potatoes are the leading commodity of highland vegetable farmers because of their high profit for farmer.  farmers in Margamulya village plant potatoes on narrow land due to limited capital, potato farming with a narrow land area is less efficient.  This study aims to analyze the use of inputs and productivity of potato farming inputs based on the area of cultivated land.  The research method used is the survey method, the data used consists of primary and secondary data, primary data is obtained from farmer, simple random sampling was used in this study.  The analysis used is descriptive analysis and mathematical analysis, which is the equation of output divided by input.  The results of the study show: Small-landed farmers use more inputs than large-landed farmers.  Farmers who grow potatoes with large areas of land are more productive than farmers who cultivate potatoes with a narrow area of land, this can be seen from the input productivity to the output of farmers with large areas of land that is higher than farmers with narrow land